Operationalizing dietary diversity: a review of measurement issues and research priorities - Ruel, Marie T. (Elsevier, 2003)
Dietary diversity (DD) is universally recognized as a key component of healthy diets. There is still, however, a lack of consensus on how to measure and operationalize DD. This article reviews published literature on DD, with a focus on the conceptual and operational issues related to its measurement in developing countries. Findings from studies of the association between DD and individual nutrient adequacy, child growth and/or household socioeconomic factors are summarized. DD is usually measured using a simple count of foods or food groups over a given reference period, but a number of different groupings, classification systems and reference periods have been used. This limits comparability and generalizability of findings. The few studies that have validated DD against nutrient adequacy in developing countries confirm the well-documented positive association observed in developed countries. A consistent positive association between dietary diversity and child growth is also found in a number of countries. Evidence from a multicountry analysis suggests that household-level DD diversity is strongly associated with household per capita income and energy availability, suggesting that DD could be a useful indicator of food security. The nutritional contribution of animal foods to nutrient adequacy is indisputable, but the independent role of animal foods relative to overall dietary quality for child growth and nutrition remains poorly understood. DD is clearly a promising measurement tool, but additional research is required to improve and harmonize measurement approaches and indicators. Validation studies are also needed to test the usefulness of DD indicators for various purposes and in different contexts.